AN ANALYSIS OF MODIFICATIONS OF AN OILFIELD PRODUCTION SYSTEM WITH TWO RESERVOIRS ON FLUID FLOW RATE - BAYU PRADANA (NIM 12205029); Pembimbing: Ir. Leksono Mucharam, M.Sc., Ph.D., ARYA
Oilfield X is producing from two different reservoirs. Production from both reservoirs are transported to the surface facilities using the same pipe network. Bottlenecking in a surface pipeline network is generally caused by flow restrictions by the pipe dimensions. The difference in reservoir pressures between the two reservoirs in oilfield X may potentially cause further bottlenecking within the system. A simple model is generated to analyze the bottleneck effect caused by the merging of two systems with differing pressures into the same pipe network. Further studies are conducted to analyze the effects of various methods designed to increase the production from both reservoirs. The results of the study confirm the presence of a bottleneck effect due to the converging of two production systems of conflicting pressures. The magnitude of this bottleneck effect is also depends on the configuration of the pipe network and pressures of both reservoirs. The methods attempted to increase the overall field flow rate are by adding a new well, installing a choke, optimization of the pipe network, and well stimulation.